Analysis of Cancer Research Projects in Sub-Saharan Africa: A Quantitative Perspective on Unmet Needs and Opportunities - Lynne Davies; Danny A. Milner; Lawrence N. Shulman; Lynnette Kyokunda; Alemayehu Bedada; Peter Vuylsteke; Nestory Masalu; Paul Jackson; Natanya Jennings; Adesumbo Odunlami; Phangisile Mtshali; Ute Dugan (JCO Global Oncology, 2023)
PURPOSETo evaluate the scope and types of cancer research projects in sub-Saharan Africa (SSA) to identify research gaps and inform future efforts.METHODSThis retrospective observational study summarized information on cancer research projects in SSA from the International Cancer Research Partnership (ICRP) between 2015 and 2020, alongside 2020 cancer incidence and mortality data from the Global Cancer Observatory. SSA cancer research projects were identified as led by investigators in SSA countries, or by investigators in non-SSA countries with collaborators in SSA, or in database keyword searches. Projects from the Coalition for Implementation Research in Global Oncology (CIRGO) were also summarized.RESULTSA total of 1,846 projects were identified from the ICRP database, funded by 34 organizations in seven countries (only one, Cancer Association of South Africa, based in SSA); only 156 (8%) were led by SSA-based investigators. Most projects focused on virally induced cancers (57%). Across all cancer types, projects were most frequently related to cervical cancer (24%), Kaposi sarcoma (15%), breast cancer (10%), or non-Hodgkin lymphoma (10%). Gaps were observed for several cancers with higher incidence/mortality burden in SSA; for example, prostate cancer accounted for only 4% of projects but 8% of cancer-related deaths and 10% of new cases. Approximately 26% were dedicated to etiology. Treatment-related research declined over the study period (14%-7% of all projects), while projects related to prevention (15%-20%) and diagnosis/prognosis (15%-29%) increased. Fifteen CIRGO projects were identified; seven were relevant across multiple cancer types, and 12 focused either wholly or partially on cancer control (representing 50% of the total research effort).CONCLUSIONThis analysis shows notable discrepancies between cancer burden and research projects and identifies opportunities for future strategic investments in cancer care in SSA.